2007
DOI: 10.1111/j.1369-7625.2007.00450.x
|View full text |Cite
|
Sign up to set email alerts
|

Patient involvement in patient safety: what factors influence patient participation and engagement?

Abstract: Background Patients can play an important role in improving patient safety by becoming actively involved in their health care. However, there is a paucity of empirical data on the extent to which patients take on such a role. In order to encourage patient participation in patient safety we first need to assess the full range of factors that may be implicated in such involvement.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

19
358
4
23

Year Published

2009
2009
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 370 publications
(404 citation statements)
references
References 31 publications
19
358
4
23
Order By: Relevance
“…24 This context clearly has implications for PPI, particularly given the identification of staff support and encouragement to patients as a key factor in the development of successful involvement practice. 46 We therefore argue that adopting a more critical approach to involvement will entail going beyond current theories ⁄ models (e.g. Health Belief Model, Theory of Planned Behaviour) that have been extensively used to predict individual patient involvement in health.…”
Section: Developing a More Critical Approach To Involvement In Patienmentioning
confidence: 99%
See 1 more Smart Citation
“…24 This context clearly has implications for PPI, particularly given the identification of staff support and encouragement to patients as a key factor in the development of successful involvement practice. 46 We therefore argue that adopting a more critical approach to involvement will entail going beyond current theories ⁄ models (e.g. Health Belief Model, Theory of Planned Behaviour) that have been extensively used to predict individual patient involvement in health.…”
Section: Developing a More Critical Approach To Involvement In Patienmentioning
confidence: 99%
“…Evidence, for example, shows that a Ôknowledge and status imbalanceÕ between patients and practitioners affects the ability of a patient to adopt safety-related behaviours. 24,46,47 Research by Peat and Entwistle et al 24 found that safety interventions which were most successful required patients and their representatives to be well informed and knowledgeable. This capacity was found to vary between individuals and to be significantly affected by educational level, income, cognitive skills and cultural differences, which might affect patients health beliefs and ability to utilize health services.…”
Section: Developing a More Critical Approach To Involvement In Patienmentioning
confidence: 99%
“…(For an alternative but congruent taxonomy on patient involvement in patient safety see Davis and colleagues. 16 ) Lyons writes from a safety engineering view about patients' role in patient safety, and moves rapidly from role to responsibility. 17 She argues that responsibility is unfair and that the patient represents an unreliable safety barrier, and attempts to encourage patients to form such a barrier are not cost-effective.…”
Section: Patient Safety: What About the Patient?mentioning
confidence: 99%
“…This supports distillation of the highly personal and non-generalizable experiences of patients preparing for TKA (Beaton & Clark, 2009). The nature of the individualistic attributes and social and group influences identified in the current research aligned with a qualitative research approach and the goal of understanding patients' sense-making (Davis, Jacklin, Sevdalis, & Vincent, 2007;Mittler et al, 2013). Furthermore, this approach recognized that the attributes were individual and not necessarily generalizable, but also assumed that a theory of cognition can be distilled from patterns within the individual patient interviews (Thompson, Locander, & Pollio, 1989).…”
Section: Methodsmentioning
confidence: 94%
“…Mittler et al (2013) introduced the importance of understanding behavioral aspects of patient encounters from the perspective of consumer psychology. Mittler et al (2013) expanded the conceptual model of patient engagement to include the social perspectives of patient activation that were first noted by Davis et al (2007). Hibbard et al (2004) identified the common behavioral theme and posited that the high personal importance of health-related decisions created a significant threshold for changes in patient behaviors.…”
Section: Empowered Behaviorsmentioning
confidence: 99%